2012
DOI: 10.1111/j.1540-8159.2011.03324.x
|View full text |Cite
|
Sign up to set email alerts
|

Late Gadolinium Enhancement CMR in Patients with Tachycardia‐Induced Cardiomyopathy Caused by Idiopathic Ventricular Arrhythmias

Abstract: LGE is a rare finding in patients with TICMP caused by idiopathic ventricular arrhythmias. LGE-CMR can be used in the diagnostic work-up of patients with TICMP. Further prospective studies are required to determine the role of LGE-CMR in predicting the recovery of left ventricular systolic dysfunction in patients with presumptive TICMP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
51
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 23 publications
7
51
0
4
Order By: Relevance
“…In 2 studies of adult patients with focal atrial tachycardia (AT), the incidence of AIC was 8.3% to 10% (5,6), whereas in a pediatric multicenter study of atrial ectopic tachycardia (AET), 28% had AIC (7). The incidence of AIC was 9% to 34% in patients with frequent premature ventricular complexes (PVCs) and/or nonsustained ventricular tachycardia referred for electrophysiological evaluation (810). …”
Section: Epidemiologymentioning
confidence: 99%
“…In 2 studies of adult patients with focal atrial tachycardia (AT), the incidence of AIC was 8.3% to 10% (5,6), whereas in a pediatric multicenter study of atrial ectopic tachycardia (AET), 28% had AIC (7). The incidence of AIC was 9% to 34% in patients with frequent premature ventricular complexes (PVCs) and/or nonsustained ventricular tachycardia referred for electrophysiological evaluation (810). …”
Section: Epidemiologymentioning
confidence: 99%
“…Of note, five patients with primary cardiomyopathy were also scanned with CMR and four of the five patients had evidence of LGE. 127 The investigators concluded that PVC-induced cardiomyopathy is less likely to have LGE on CMR as compared with other forms of cardiomyopathy. Consistent with this finding, a recent canine model of PVC-induced cardiomyopathy failed to demonstrate increased inflammation, fibrosis or changes in apoptosis or mitochondrial function.…”
Section: Imaging Studies In Tachycardia-induced Cardiomyopathymentioning
confidence: 99%
“…This suggested that tachycardia-induced cardiomyopathy may have been involved in the decreased cardiac function. However, because LGE of CMRI is usually unobserved in tachycardia-induced cardiomyopathy,29 30 we cannot explain the LGE positivity in our patient. In addition, as IVCD was noted 3 years earlier, we presume that the patient may have experienced cardiomyopathy that caused latent myocardial damage.…”
Section: Discussionmentioning
confidence: 66%